DAMPAK CORONA VIRUS DISSEASE (COVID-19) TERHADAP PENJUALAN ANGGREK BULAN (Phalaenopsis amabilis) PADA PEDAGANG BUNGA TRADISIONAL DI DENPASAR. - Ananda Wiguna I Made (AGRICA, 2021)
In the midst of the Covid-19 pandemic outbreak that is happening in Indonesia, many impacts are happening to the economy of the Indonesian people, one of which is the orchid plant trader in Denpasar City. This study aims to analyze the percentage of orchid sales in the month before the pandemic and during the Covid-19 pandemic and to find out the impact caused by the Covid-19 pandemic on the sales of moon orchids in Denpasar. The results showed that the total sales of orchids in the month before the pandemic were 3,800 trees, while the sales of orchids for the month of the pandemic in 2020 amounted to 925 so that there was a decrease of 75.65%. There is a significant difference between the receipt of sales of orchids in the months before the Covid-19 pandemic and during the Covid-19 and the impact of the Covid-19 pandemic on the sales of moon orchids, namely the decline in sales caused, among others, a decrease in tourists, the number of hotels closed, the elimination of major events so that causing a reduction in the circulation of money in the province of Bali, including in Denpasar. Keywords: Phalaenopsis amabilis , Sales, Covid-19 Pandemic